2021
DOI: 10.3389/fonc.2021.724655
|View full text |Cite
|
Sign up to set email alerts
|

Super-Enhancer Induced IL-20RA Promotes Proliferation/Metastasis and Immune Evasion in Colorectal Cancer

Abstract: Unveiling key oncogenic events in malignancies is the key to improving the prognosis and therapeutic outcome of malignancies. Lines of evidence have shown that super-enhancers control the expression of genes that determine the cell fate, but the oncogenic super-enhancers in colorectal cancer (CRC) and their impact on carcinogens remain largely unexplored. Here, we identified a new oncogenic super-enhancer-regulated gene, IL-20RA, in CRC. Using the integrative analysis of H3K27ac ChIP-seq and RNA-seq in CRC tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The inflammatory immune role of eRNA in tumors was first reported by Chen et al ( 99 ), demonstrating that H. pylori stimulate bromodomain-containing factor Brd4 recruitment to the BIRC3 enhancer, which promotes BIRC3 eRNA synthesis and cIAP2 expression, which inhibits caspase-3 activation and enhances apoptosis resistance in gastric epithelial cells. Additionally, some studies have suggested the presence of oncogenic SEs in colorectal cancer and confirmed their involvement in regulating oncogenic and immune pathways in colorectal cancer by modulating IL-20RA expression, affecting cell proliferation and immune evasion-related gene ecpression ( 162 ). Pancreatitis accelerates Kras mutation-driven tumorigenesis in mice, which is mostly found in pancreatic ductal adenocarcinoma ( 163 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The inflammatory immune role of eRNA in tumors was first reported by Chen et al ( 99 ), demonstrating that H. pylori stimulate bromodomain-containing factor Brd4 recruitment to the BIRC3 enhancer, which promotes BIRC3 eRNA synthesis and cIAP2 expression, which inhibits caspase-3 activation and enhances apoptosis resistance in gastric epithelial cells. Additionally, some studies have suggested the presence of oncogenic SEs in colorectal cancer and confirmed their involvement in regulating oncogenic and immune pathways in colorectal cancer by modulating IL-20RA expression, affecting cell proliferation and immune evasion-related gene ecpression ( 162 ). Pancreatitis accelerates Kras mutation-driven tumorigenesis in mice, which is mostly found in pancreatic ductal adenocarcinoma ( 163 ).…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, a decrease in MYC mRNA was found on the knockdown of the corresponding eRNA ( 158 ). JQ1 was demonstrated to decrease the transcriptionally activated eRNAs of SEs, causing the down-regulation of IL-20RA expression and inhibition of growth, metastasis and immune escape in colorectal cancer ( 162 ). Therefore, JQ1 regulates enhancer transcription and eRNA synthesis by affecting the mediator complex, which regulates the downstream target genes to modulate the disease process.…”
Section: Resultsmentioning
confidence: 99%
“…SEs were initially discovered in embryonic stem cells (ESCs), with ESC-specific master transcription factors Oct4, Sox2, and Nanog binding to enhancer elements and recruiting mediators to activate the gene transcription program 12 . Subsequently, SEs were identified in other cells, including cancer cells 13,14 . As novel epigenetic regulatory elements, SEs precisely regulate oncogene transcriptional activation during tumorigenesis and may be potential therapeutic targets 15,16 .…”
Section: Overview Of Superenhancers Characteristics and Identificatio...mentioning
confidence: 99%
“…However, only a subset of patients responed to immunotherapy whereas others show minimal or no response because of variations in the complex tumor immune microenvironment [24]. The immune response of digestive system tumors is also regulated by SEs [25]. A Recent study showed that SEs promote chemoresistance of tumors by aberrant transcription of genes involved in chemoresistance [26].…”
Section: Biological Functions Of Sesmentioning
confidence: 99%
“…In breast cancer, CD47 expression is upregulated by a CD47-associated SE [72]. The upregulation of SE-regulated IL-20RA is associated with increased immune evasion of CRC cells through oncogenic and immune response pathways that reduce infiltration of N1 neutrophils, M1 macrophages, and T cells [25].…”
Section: Regulation Of Immune Evasionmentioning
confidence: 99%